Pengaruh Hedonistic Lifestyle dan Impulse Buying Terhadap Layanan Paylater dengan Literasi Keuangan Sebagai Pemoderasi - Puspitasari, Dian; Trisnaningsih, Sri (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
Paylater services are becoming increasingly popular among Generation Z as a fast and practical payment alternative. However, the growing use of these services raises concerns about potential consumerist behavior and poor financial decision-making. This study aims to examine the influence of hedonistic lifestyle and impulse buying on the decision to use paylater services, and analyze the role of financial literacy as a moderating variable. The research was conducted at IKIP PGRI Bojonegoro with a total of 87 student respondents selected through purposive sampling. A quantitative research method was used with a survey approach and data were analyzed using the PLS-SEM technique through SmartPLS 4.0 software. The results show that hedonistic lifestyle and impulse buying have a significant influence on the decision to use paylater services. Furthermore, financial literacy was found to significantly moderate and weaken the effect of hedonistic lifestyle on the decision to use paylater services. However, financial literacy does not significantly moderate the relationship between impulse buying and paylater usage decisions. These findings suggest that a good understanding of financial concepts can reduce the impact of a hedonistic lifestyle on paylater usage decisions, but is not sufficient to control the emotional impulse associated with impulsive buying behavior.